2013
DOI: 10.1017/s1368980013001821
|View full text |Cite
|
Sign up to set email alerts
|

Public beliefs about the causes of obesity and attitudes towards policy initiatives in Great Britain

Abstract: Objective: To assess attributions for overweight and the level of support for policy initiatives in Great Britain. Design: Cross-sectional. Respondents indicated their agreement (5-point scales: strongly disagree to strongly agree) to three potential causes of overweight (environment, genes, willpower) and five policies (free weight-loss treatment, taxing unhealthy foods, healthy lifestyle campaigns, food labelling, advertising restrictions). Setting: Data were collected as part of a computer-assisted, face-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 26 publications
5
86
2
Order By: Relevance
“…A 2012 omnibus survey in the UK also found less support for taxation-based policies (32%), and more support for food labelling (66%) and advertising restrictions (57%). 17 Similarly, an Australia-wide study in 2010 found higher levels of support for a 'trafficlight' style of labelling (87%) and restrictions on advertising unhealthy food to children on television (83%) than taxing unhealthy foods and using the money for health programs (62%). 9 That study reported stronger support for increasing the price of unhealthy foods to reduce the cost of healthy foods (71%) than our study, although a direct comparison cannot be made because more contextual information was provided leading up to each question in the 2010 study (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A 2012 omnibus survey in the UK also found less support for taxation-based policies (32%), and more support for food labelling (66%) and advertising restrictions (57%). 17 Similarly, an Australia-wide study in 2010 found higher levels of support for a 'trafficlight' style of labelling (87%) and restrictions on advertising unhealthy food to children on television (83%) than taxing unhealthy foods and using the money for health programs (62%). 9 That study reported stronger support for increasing the price of unhealthy foods to reduce the cost of healthy foods (71%) than our study, although a direct comparison cannot be made because more contextual information was provided leading up to each question in the 2010 study (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…32, nº 2 (mayo) have suggested that emphasising the role of the food environment in causing obesity may promote health behaviours without imposing the negative consequences associated with the beliefs about obesity is under personal control (Pearl & Lebowitz, 2014). For example, it has been found that only the belief that obesity is caused by external causes was associated with support for government policies to prevent and treat overweight which gives an idea about how obese people are blamed by Society about their condition (Beeken & Wardle, 2013). Finally, in a more individual level, it is also important to remark that it has been suggested that to assess individuals' beliefs about the causes of obesity when following a diet is a very important issue (Barberia, Attree, & Todd, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Psychological symptoms such as depression and anxiety, to feel not to have any energy and stress diminish the quality of life. In addition to the unpleasant situations obese persons suffer from various social negative attitudes (Beeken and Wardle, 2013;Poon and Tarrant, 2009;Schwartz and Puhl, 2003;Uluöz E., 2016a;Yılmaz C.Y., 2009). Several researches show that participation in a physical activity can help solving some of these problems (Bauman, 2004;Daley et al, 2007;Penedo and Dahn, 2005;WHO, 2000) In principle, the human body is designed to be in movement.…”
Section: Introductionmentioning
confidence: 99%